Análise da lucratividade de cliente: pesquisa intervencionista em uma indústria de bebidas - Pereira, Bruno Vanderlei (2019)
Purpose: This study aims to develop and analyze customer profitability in a beverage industry. The beverage market has a high level of supply and a customer can be loyal without details. Thus, it becomes very important to identify how the company's management control processes are and why something is credited and innovative for a company, or the focus on analyzing customer profitability is of the utmost importance for decision making and contribution with as company strategies. As a result, this study has the ability to research the strengths and those that customers of self-service channels and distributors can bring about the bottom line. Literature/methodology/approach: The literature was reviewed to support the principles of management control system, customer profitability, family business control, learning and decision-making theories. Given this, a fieldwork was carried out in the company that had the phenomenon to be studied. Initially, interviews were conducted with the main people related to the subject in order to understand the industrial process, customer characteristics and difficulties linked by each customer before performing an operation. Then, 7 self-service customers and 6 distributor-profile customers who had carried out operations from January to July 2019 were selected, in order to leave the search balanced and with the same parameter for all customers. The efforts that customers demanded from the company under study were measured and presented in a P&L. Findings: The main results analyzed show that for self-service clients, selling expenses with relationship agreement and fixed expenses stipulated in contracts end up having a marked negative impact on the result and negotiation processes tend to be very complex without these types of expenses, On the other hand, the visibility that this type of channel provides makes the product always in evidence in the market. For distributing customers, the operation tends to lead to many discounts with product bonuses, yet the results related to operating margin achieve advantage when compared to the self-service channel but are disadvantaged when the criterion is brand visibility and disclosure. Practical implications: Beverage companies tend to be in a very competitive market where success / profit is often tied to cents, so having a report that is able to present customer profitability separates by acting channels, the chance becomes big and evident to have improvements in management controls and consequently in strategic decisions. Such analysis allows us to identify the chance of having the characterization of each customer and how much it may be profitable or not for the company and can even be identified if it makes sense to continue making sales to a particular customer. Originality and contributions: For the company terms, this research made a real contribution and was original mainly because they did not have a management control in the form of a report demonstrating customer profitability. Being able to have real numbers and conditions by analyzing and identifying who really ensures profitability for the company. The findings of this research shed light on the real importance of these analyzes by meeting the characteristics exposed in the academic setting.